Occurrence and Characteristics of Livestock-Associated Methicillin-Resistant Staphylococcus aureus in Quarter Milk Samples From Dairy Cows in Germany - Kadlec, Kristina; Entorf, Monika; Peters, Thomas (Frontiers in Microbiology, 2019)
The aim of this study was to identify and characterize LA-MRSA in a very recent collection of staphylococci isolated from bovine quarter milk samples. All milk samples (n=14,924) sent to the MBFG in March 2017 were included into this study. The samples originated from 3,887 cows with 3,367 samples from 2,280 animals being positive for bacteria, prototheca and/or yeast. The second most common infectious agent was Staphylococcus and 659 isolates were investigated. Staphylococcus aureus was confirmed by PCR for the spa gene. A CC398-specific PCR was performed for all S. aureus isolates. Susceptibility to penicillin was tested for all isolates by agar disk diffusion. All oxacillin resistant isolates were analyzed by microarray and tested for their susceptibility to 30 antimicrobial agents. Of the isolates 372 were S. aureus from Germany with 214 isolates being not epidemiologically related. Among the independent isolates nine were identified as oxacillin resistant. In addition five isolates epidemiologically related to these nine were MRSA. One of them showed differences to the other MRSA isolate from the same farm resulting in altogether ten different MRSA isolates. All ten belonged to the clonal complex CC398. These ten LA-MRSA isolates had three to six antimicrobial resistance genes. The gene mecA was in all cases located on a SCCmec V element. Among the remaining S. aureus 11 isolates belonged to CC398. In conclusion this study showed a high detection rate of staphylococci in bovine quarter milk samples. In contrast MRSA was rarely detected and belonged in all cases to CC398. Only 11/358 MSSA (3.1%) belonged to this CC.